Exploring reflective practice in clinical nursing education among nurse educators - Azmi, Barkhis; Atan, Ashikin; Mohd Ali, Noor Azizah; Lee, Siew Pien; Zolkefli, Yusrita (UPM Press, 2024)
Introduction: Reflective practice is a recommended approach to boost excellence in clinical nursing education frameworks. Despite its significance, the literature on this practice among nurse educators is scarce, and the comprehensive exploration of it is inadequate. Thus, this study aims to assess nurse educators’ level of reflective thinking and their perception, understanding, and attitudes towards reflective practice in clinical nursing education. Methods: A mixed-method study employing a questionnaire (n = 221) was conducted among nurse educators in Ministry of Health Training Institutions across Malaysia between April and May 2022. Convenience sampling was used, and questionnaires were distributed online. The questionnaires included 16-item scales to measure reflective thinking using a 5-point Likert scale adapted from a previous study and 16 items consisting of closed-ended and open-ended questions. Quantitative data were analysed using descriptive statistics (SPSS version 26), while qualitative data underwent content analysis. Results: The study discovered that despite the high level of reflective thinking among nurse educators (mean score 4.00 ± 0.38), their inadequate understanding of the purpose of reflective practices integration into clinical nursing education led them to focus on the practice which barely benefit the learning process. However, the positive attitudes towards training indicate their willingness to enhance their knowledge and skills in this area, possibly contributing to the further development of reflective practice in clinical nursing education. Conclusion: Targeted training programmes and educational initiatives should be designed to address the gaps identified in this study and enhance reflective practices in clinical nursing education.